An Operational Measure of Liquidity - Lippman, Steven A.; McCall, John J. (American Economic Review, 2016)
Embedding the process of selling an asset in a search environment enables one to provide an exact definition of liquidity: an asset's liquidity is the expected time until it is sold while pursuing an optimal (in the sense of maximization of expected discounted net proceeds) policy. This analysis reveals that this definition is compatible with most other notions of liquidity and, in particular, with those of John Maynard Keynes, impatience, the discount associatedwith a quick sale, predictability, and flexibility. Copyright 1986 by American Economic Association.